Determinants of Frequency and Content of Antenatal Care in Postnatal Mothers in Arba Minch Zuria District, SNNPR, Ethiopia, 2019 - Haile, Dereje (Int J Womens Health, 2020)
BACKGROUND: Antenatal care is one of the strategies for reducing maternal morbidity and mortality directly by affording increased chances of early detection of high-risk pregnancies. WHO recommends a minimum of four ANC visits. In order to make it effective, monitoring of the content and quality of the ANC is needed. However, a number of studies focus on the frequency of ANC, and evidence on core contents of the ANC was limited in this study area. The aim of this study was to determine factors associated with content of the ANC. METHODS AND MATERIALS: A cross-sectional study design was employed to collect data from a total of 432 respondents by using a semi-structured questionnaire. Data were entered in EpiData version 3.1 and exported to SPSS version 20 for analysis. Both binary logistic regression and generalized linear regression with Poisson type were applied to determine factors associated with frequency of the ANC and core contents of ANC, respectively. RESULTS: The majority of the mothers (78.7%) visited first ANC lately, and 25.2% of mothers attended ≥4 ANC visits. Only 17.1% of mothers received all the eight selected elements of ANC services. Predictors of the core contents of the ANC were the frequencies of ANC (AOR: 0.84 (95%CI: 0.76–0.93), pre-pregnancy utilization of contraception (0.63 (95%CI: 0.55–0.72)), pregnancy desire (AOR: 0.82 (95%CI: 0.71–0.94), and birth preparedness and complication readiness (AOR: 0.90 (95%CI: 0.82–0.98). CONCLUSION: This study found that low level of WHO minimum recommended ANC and core contents of the ANC. This study suggests that identifying pregnant mothers early increases frequency of the ANC, which improves core content of care.